Materials engineering and manufacturing : selected peer-reviewed full tet papers from the 9th Asia Conference on Mechanical and Materials Engineering (9th ACMME) and 6th International Conference on Civil Engineering and Materials Science (6th ICCEMS) - Es-Said, Omar S. (Trans Tech Publications, Limited, 2021)
Selected peer-reviewed full text papers from the 9th Asia Conference on Mechanical and Materials Engineering (9th ACMME) and 6th International Conference on Civil Engineering and Materials Science (6th ICCEMS).
Palm Kernel Shell as Partial Coarse Aggregate Replacement in Asphalt Mixture: Optimum Binder Content and Volumetric Properties Investigation.
Keywords: Materials -- Congresses.; Materials science -- Congresses.; Mechanical engineering -- Congresses.; elektronické knihy; electronic books